2000
DOI: 10.1038/sj.mp.4000771
|View full text |Cite
|
Sign up to set email alerts
|

Leptin suppresses semi-starvation induced hyperactivity in rats: implications for anorexia nervosa

Abstract: Semi-starvation induced hyperactivity (SIH) occurs in rodents upon caloric restriction. We hypothesized that SIH is triggered by the decline in leptin secretion associated with food restriction. To test this hypothesis, rats, which had established a stable level of activity, were treated with leptin or vehicle via implanted minipumps concomitantly to initiation of food restriction for 7 days. In a second experiment treatment was initiated after SIH had already set in. In contrast to the vehicle-treated rats, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
138
2
11

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(165 citation statements)
references
References 27 publications
13
138
2
11
Order By: Relevance
“…This body weight loss itself might also trigger hyperactivity. Indeed, it was hypothesized before that a decrease in plasma leptin levels associated with body weight loss might trigger hyperactivity [8]. In the present experiment it was observed that body weight loss was correlated with RWA in rats without a plate and that the presence of a warm plate reduced body weight loss.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This body weight loss itself might also trigger hyperactivity. Indeed, it was hypothesized before that a decrease in plasma leptin levels associated with body weight loss might trigger hyperactivity [8]. In the present experiment it was observed that body weight loss was correlated with RWA in rats without a plate and that the presence of a warm plate reduced body weight loss.…”
Section: Discussionsupporting
confidence: 63%
“…However, although body weight loss was significantly affected by access to a warm plate, plasma leptin levels were still undetectable and no differences in leptin expression levels in WAT were observed. This suggests that heat treatment in ABA overrules the putative role of decreased leptin levels in triggering hyperactivity [8].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Basal body temperature of ad libitum-fed rats was not altered following chronic olanzapine treatment, which is in contrast with another study reporting dose-dependent hypothermia following acute olanzapine treatment in ad libitum-fed rats (Oerther and Ahlenius 2000). It has previously been shown that peripheral leptin treatment reduced hyperactivity of rats exposed to the semistarvation-induced hyperactivity model (Exner et al 2000), and it was proposed that decreases in leptin signaling might trigger hyperactivity in rats, as well as in AN patients (Hebebrand et al 1997). In our study, plasma leptin levels were undetectable in both vehicle-and olanzapine-treated ABA rats.…”
Section: Discussionmentioning
confidence: 48%
“…Animal models of ''anorexia based activity'' exist 54 and both rodent and human studies indicate that hypoleptinemia is associated with hyperactivity and motor restlessness. 55,56 In food restricted rats, exogenous leptin suppresses the development of semi-starvation induced hyperactivity 57 ; in AN patients leptin levels are inversely correlated with motor restlessness. 58 The optional inclusion of symptoms of elevated activity would allow reference to a biologically based phenomenon, which appears rather specific to AN.…”
Section: Physical Activitymentioning
confidence: 99%